Testing and estimation of calculation components influence on metrologycal properties of gas flow metering devices - Petryshyn, I. S.; Bezghachniuk, Ya. V.; Petryshyn, N. I.; Bas, O. A. (Visnyk of Vinnytsia Politechnical Institute, 2014)
Based on international experience the paper analyzed the methods and means testing and trial of computer components included in the composition standard prover gas volume and flow rate reproduction, gas meters calibration prover, gas vo-lume correctors. The necessity to assess the quantitative characteristics of algorithms gas calculation that are tested to establish criteria for assessing their impact on the metrological characteristics of measuring instruments is substantiated in the paper. Details and components of the random error of rounding input that may affect their metrological characteristics are estimated. The procedure of the software testing within the working standards (gas meters calibration prover) and work-ing measuring equipment (gas volume correctors) during the state metrological attestation is described in the paper.